Spin multistability in dissipative polariton channels - Bozat, Ö. (2013)
We present a model for the theoretical description of the dynamics of a system of spinor cavity polaritons in real space and time, accounting for all relevant types of the interactions and effective magnetic fields. We apply our general formalism for the consideration of the polarization dynamics of the coherently driven, one-dimensional polariton channel. We investigate the effect of the temperature and the longitudinal-transverse splitting on the spin (polarization) multistability and hysteresis arising from the polarization-dependent polariton-polariton interaction. We show that the effect of the phase of the driving laser pump is as important as its strength, and demonstrate that the multistability behavior can survive up to high temperatures in the presence of longitudinal-transverse splitting.